The Baha'i faith in Africa : establishing a new religious movement, 1952-1962 - Lee, Anthony A., 1947- (Studies of Religion in Africa, 2011)
In 1952, there were probably fewer than 200 Baha'is in all of Africa. Today the Baha'i community claims one million followers on the continent. Yet, the Baha'i presence in Africa has been all but ignored in academic studies up to now. This is the first monograph that addresses the establishment of this New Religious Movement in Africa. Discovering an African presence at the genesis of the religon in Iran, this study seeks to explain why the movement found an appeal in colonial Africa during the 1950s and early 1960. It also explores how the Baha'i faith was influenced and Africanized by its new converts. Finally, the book seeks to make sense of the diverse and contradictory American, Iranian, British, and African elements that established a new religion in Africa.